Racial diversity in the suburbs: how race-neutral responses to demographic change perpetuate inequity in suburban school districts. Issue 4 (3rd July 2016) - Diem, Sarah; Welton, Anjalé D.; Frankenberg, Erica; Jellison Holme, Jennifer
Abstract : Suburbs across the US are experiencing dramatic demographic shifts, yet there is little research available on how suburban school districts are dealing with these changes. In this article, we examine the discourses surrounding race and demographic change in three suburban school districts that have been undergoing rapid demographic changes and which contain demographically distinct areas within their district boundaries. Utilizing a critical discourse analysis (CDA) approach, we analyze how the policy context (federal and state) frames actors' discourses and understandings of race, paying particular attention to the political and institutional factors affecting school policy. We illustrate how the discourse, in turn, is related to the actions (or inactions) taken by district and school leaders to respond to demographic change. We conclude the article by discussing policy implications and potential challenges districts may face in the future if efforts to purposively address racial changes continue to be avoided.